2016
DOI: 10.1016/j.toxrep.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of grape seed proanthocyanidins on Cadmium-induced hepatic injury in rats: Possible involvement of mitochondrial dysfunction, inflammation and apoptosis

Abstract: The present study was undertaken to evaluate the possible ameliorative role of grape seed proanthocyanidins (GSP) against Cadmium (Cd) induced hepatic inflammation, apoptosis and hepatic mitochondrial toxicity in rats. Male Wistar rats were distributed in four experimental groups: control, GSP, Cd and Cd + GSP. Exposure to a hepatotoxic dose of Cd (5 mg/kg BW) caused liver damage, coupled with enhanced reactive oxygen species (ROS) generation, increased inflammation and apoptosis in liver with increased DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…Resveratrol inhibited the F-type ATPase by targeting the F1 sector, which is located in the inner membrane of mitochondria and the plasma membrane of normal endothelial cells and in several cancer cell lines (Zheng et al;1999, Dorrie et al;. Resveratrol has been shown to improve mitochondrial function (Miltonprabu et al;.…”
Section: Mitochondrial Pathwaymentioning
confidence: 99%
“…Resveratrol inhibited the F-type ATPase by targeting the F1 sector, which is located in the inner membrane of mitochondria and the plasma membrane of normal endothelial cells and in several cancer cell lines (Zheng et al;1999, Dorrie et al;. Resveratrol has been shown to improve mitochondrial function (Miltonprabu et al;.…”
Section: Mitochondrial Pathwaymentioning
confidence: 99%
“…Hepatoprotective effect of grape seed proanthocyanidins were also detected against cadmium induced toxicity in rats [29]. Tri-carboxylic acid cycle enzymes, increased mitochondrial swelling, inhibition of cytochrome c oxidase activity and complex I-III, II-III and IV mediated electron transfer, decreased mitochondrial ATPases, a reduction in calcium content and mitochondrial oxygen consumption were restored at ordinary levels by grape seed proanthocyaninds following cadmium exposure [29]. However, grape juice concentrate did not modulate metalloproteinases (MMPs) 2 and 9 immunoexpression in cadmium-intoxicated rats [30].…”
Section: Livermentioning
confidence: 99%
“…For example, celluar reduced glutathione (GSH) depletion mediated Cd‐induced PTEN degradation and subsequent PI3K/Akt activation and then induced inflammation in RAW264.7 cells (Huang et al, ). In another study, Cd (5 mg/kg body weight) caused enhanced reactive oxygen species (ROS) generation, increased inflammation and apoptosis (Miltonprabu et al, ). Moreover, it has been reported that maternal exposure to Cd led to accumulation in placental tissues and correlated with increased nuclear factor‐kappaB expression, which was sensitive to inflammation and oxidative stress (Ronco et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that acute/subacute Cd exposure led to oxidative stress and endoplasmic reticulum (ER) stress in different organs (Gobe & Crane, 2010;Ji et al, 2011;Ji et al, 2012;Kitamura & Hiramatsu, 2010;Li et al, 2016). It has also been reported that acute Cd exposure can induce inflammation through oxidative stress mechanisms (Dong et al, 1998;Huang et al, 2014;Miltonprabu et al, 2016;Ronco et al, 2011). For example, celluar reduced glutathione (GSH) depletion mediated Cd-induced PTEN degradation and subsequent PI3K/Akt activation and then induced inflammation in RAW264.7 cells (Huang et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation